Awareness and knowledge of takaful in Malaysia: a survey of Malaysian consumers - Hassan, Rusni; Salman, Syed Ahmed; Kassim, Salina; Ab Rashid, Hafiz-Majdi (Center for Promoting Ideas, USA, 2018)
Insurance, nowadays, is no longer a luxury rather a necessity. Government regulations and employment are two very important factors that contribute to the huge overall growth of the insurance industry because they force general public to buy it. The concept behind conventional insurance is contrary to the principles of Islam and socio-ethical perspective. The purpose of Shari’ah is to create and maintain a harmonious social environment by moulding our conducts in all aspects of our ritual and daily life.Takaful industry remains to be relevant even after three decades of its introduction due to the continuous demands from the multiracial and multi-ethnic participants from various backgrounds. The said industry celebrates the contributions of their stakeholders, namely the Takaful operators, Shari’ah advisors and the participants or customers. Additional credit for the progressive development of Takaful industry goes to the consistent guidelines from the regulators. However, one factor that hinders further development of Takaful industry is the lack of awareness of its presence and purpose in Malaysian market. Therefore, this paper was designed to examine the knowledge and awareness of Takaful among Malaysian consumers in Malaysia by collecting primary data through survey questionnaires. Out of the 600 questionnaires that were sent to consumers in greater Malaysia i.e. Kuala Lumpur and Selangor, we received 503 questionnaires. Random selection was used to select the sample from the known population. The findings show that out of the 503 respondents, 124 have no knowledge of Takaful and 45% are not aware that Takaful policy holders share risks mutually. Also, 33.2, %, 38.8% and 37.2% do not know that Takaful is free from gambling, uncertainty, and interest.70.2% respondents, however, think that Takaful products comply with Shari’ah.